Evaluation of diagonal earlobe crease (Frank's sign) as a non-invasive marker of cardiovascular diseases - Lakshmi Manasa U; P.S.N. Murthy (Al Ameen Medical College, 2021)
Background: Cardiovascular diseases are the leading cause of death worldwide. Efforts for early diagnosis of cardiovascular diseases have compelled many clinicians to look for simple and non-invasive markers like diagonal ear lobe crease. Objectives: The aim of this study is to identify the prevalence of DELC and to determine the association of diagonal earlobe crease (DELC) with cardiovascular diseases. Methods: This was a case-control study conducted on two hundred participants in a tertiary care hospital. The participants were examined for the presence of DELC on both the ears and the severity of the crease was assessed. Results: The prevalence of DELC was 72% in cases and 17% in controls. Statistically significant association was found between DELC and cardiovascular diseases (P<0.0001).The sensitivity and specificity for DELC to predict cardiovascular diseases was 72% and 83% respectively. The odds of development of cardiovascular diseases in an individual with DELC (both unilateral and bilateral) was 12.55 times greater than an individual without DELC. Conclusion: DELC can be used as a simple and feasible screening tool for early diagnosis and prevention of cardiovascular diseases.